Factores de Riesgo de la ludopatía, en los adolescentes del colegio N° 80627 Leoncio Prado Gutiérrez, distrito El Porvenir, año 2015. - Bermudez Zevallos, Magdalena Anita (2016)
This research seeks to understand the factors that create vulnerability in the development of pathological gambling against technology, teenagers Gutierrez Prado district of El Porvenir Leoncio College. The sample was made up of 84 adolescent male and female between the ages of 12-17 years. It was considered as a reference theories make it possible to better explain the problem of study hypothesizing and / or objective of studies that best summarizes research. They know the methodology used in collecting information, which was subject to analysis because, it followed the results were expressed in statistical tables that reflect each of the variables and indicators research subject in detail. In the results and discussion highlights the characteristics of the population subject of study which is made up of a group of teenagers whose ages shear between 11 to 16 years who are studying at the secondary level, then it will be released social factors that generate vulnerability in the development of pathological gambling technology front formed by the influence of the peer group s and the use and access to Xbox games or the Internet. Also in the family that generate vulnerability factors in the development of pathological gambling against technology consists of family dynamics, family conflicts and coping parento problems